Analysis and Correction of Tooth Deformation of the Herringbone Gear with Electron Beam Welding - Guan Rongxin; Ding Yinghui; Qin Lei; Zhao Yukai; Miao Weiwei (Jixie chuandong)
Taking the electron beam welding process as an example,the tooth profile analysis of the split type herringbone gear is carried out after the deformation of the diameter direction. Finally,the problem of the machining of the herringbone gear without the retreating slot is solved. Through the relation of tooth involute,base circle,radius of curvature,pressure angle and helix angle,the change law of tooth profile and spiral line in the condition of gear diameter deformation is studied,and the influence of the change of diameter on pressure angle,spiral angle and the second influence of the change of spiral angle on the tooth shape are analyzed. The formula for calculating deformation is derived,and the composite deformation amount and the composite deformation and tooth helical line deformation amount of the tooth profile due to change of diameter are calculated,the basis for the reverse compensation of the grinding teeth before welding is provided. Finally,the above analysis is verified by an example,and the calculation method is not limited to the electron beam welding process.